Effects of active video games on physical activity among overweight and obese college students: a systematic review - Zhao, Yue; Soh, Kim Geok; Abu Saad, Hazizi; Liu, Chunqing; Ding, Cong (Frontiers Media SA, 2024)
Background: The purpose of this study was to critically review the existing literature on the effects of active video games (AVGs) on physical activity in overweight and obese college students to determine whether AVGs can promote and achieve recommended levels of physical activity. The results should provide constructive input for future research. Methods: A total of five international databases including PubMed, SCOPUS, Web of Science, CINAHL Plus, and EBSCOhost were searched with keywords related to “active video games,” “physical activity,” and “obese college students” from July 2022. A systematic review was conducted using the PRISMA guidelines and randomised controlled trial (RCT) studies that met the inclusion criteria were included. Furthermore, the quality assessment of the studies was measured using the PEDro scale. Results: One thousand and twenty-three articles were retrieved, of which eight randomised controlled trial studies met the inclusion criteria. AVGs can reduce sedentary behaviour and positively affect physical activity, time spent on moderate-to-vigorous physical activity (MVPA), positive psychological factors, and game attendance rate. Combining AVGs with other assistive devices (such as mini-trampolines and stationary bikes) can enhance the effects of AVGs and provide greater physiological stimulation. Different types of AVGs and game modes can achieve different emotional responses, physiological stimulation, and physical activity levels. Conclusion: The research findings prove that AVGs can be a viable intervention to increase physical activity in overweight or obese college students, ultimately reaching the recommended physical activity level(PAL). Physical activity can be further increased by incorporating assistive devices or using features supported by self-determination theory (SDT). As a new modality, AVGs could be a potential alternative to traditional physical activity.